Aspidistra erosa, A. sarcantha, and A. verruculosa (Asparagaceae), three new species from Vietnam - Averyanov, Leonid V.; Le, Tuan Anh; Nguyen, Khang Sinh; Tillich, Hans Juergen; Nguyen, Danh Duc; Anh Hoang, Le Tuan; Tran, Hoang Dung; Thanh Dat, Pham Thi; Maisak, Tatiana V. (Phytotaxa, 2019)
The genus Aspidistra Ker-Gawler (1822 plate 628), overlooked for decades, is recently remarkably fast growing. During the past decade, about 90 species new to science were discovered and described, mainly from southern China, Vietnam, and Laos. With its diversity in flower morphology Aspidistra is among the most spectacular genera of Monocotyledons. Vietnam turned out to be especially rich in Aspidistra species (Tillich 2014), and at, least 30 additional species were discovered and described recently in this country (Averyanov & Tillich 2014, 2015, 2016, 2017, Leong-Skornickova et al. 2014, Vislobokov et al. 2014a, b, 2016a, b, 2017, Vislobokov 2015, 2016, Olivier 2015, Averyanov et al. 2016, 2017, 2018a, b, Nguyen et al. 2017, Tillich et al. 2017, Tillich & Averyanov 2018). Meanwhile, the diversity of the genus in Vietnam remains insufficiently inventoried. Below we describe three more new species from central Vietnam.